2022
DOI: 10.3389/fpsyg.2022.747296
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Filial Piety and the Academic Achievement and Subjective Wellbeing of Chinese Early Adolescents: The Moderated Mediation Effect of Educational Expectations

Abstract: A successful student has been defined as one who not only performs well in academics but is also happy. Hence, how to promote adolescents’ academic success and wellbeing is an important issue with which researchers have been concerned. A few studies have explored the relationship of filial piety to the academic achievement or life satisfaction of Chinese adolescents. However, in view of the close relationship between the two outcomes, the unique effects of filial piety on academic achievement and subjective we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 88 publications
(152 reference statements)
0
8
0
Order By: Relevance
“…Collectivism, in contrast, imparts collectivist thinking, whereby individual attainment (e.g., enrollment in medical school) is simply not for one's own self-gratification. Existing literatures often associate the position of collectivism with the theoretical concept of "filial piety" (W. W. Chen & Ho, 2012;Chow & Chu, 2007;Guo et al, 2022;Tam, 2016), which emphasizes the importance of family values, social relationships, and fulfillment of dutiful obligations.…”
Section: What Is the Self? A Brief Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectivism, in contrast, imparts collectivist thinking, whereby individual attainment (e.g., enrollment in medical school) is simply not for one's own self-gratification. Existing literatures often associate the position of collectivism with the theoretical concept of "filial piety" (W. W. Chen & Ho, 2012;Chow & Chu, 2007;Guo et al, 2022;Tam, 2016), which emphasizes the importance of family values, social relationships, and fulfillment of dutiful obligations.…”
Section: What Is the Self? A Brief Introductionmentioning
confidence: 99%
“…Existing literatures often associate the position of collectivism with the theoretical concept of “filial piety” (W. W. Chen & Ho, 2012; Chow & Chu, 2007; Guo et al, 2022; Tam, 2016), which emphasizes the importance of family values, social relationships, and fulfillment of dutiful obligations.…”
Section: What Is the Self? A Brief Introductionmentioning
confidence: 99%
“…The filial piety, which has been formed in China for a long time, has a significant impact on residents' SWB. [5][6][7] Since Confucius established the connotation of filial piety as "serving parents well," filial piety has been promoted by the ruling class, demonstrated by the intellectual class, and practiced by the general public in the long traditional society. [8] In the modern China, most of studies focus on how filial piety should be adapted to the status and value concepts of modern people.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Yuan analyzed relationship between intergenerational co-residence and the SWB of elders based on the individual-level panel data collected from the Chinese Longitudinal Healthy Longevity Survey from 2002 to 2014. [6] Guo et al [7] uncovered the relationship of filial piety to the academic achievement or life satisfaction of Chinese adolescents. If we only discuss how to adapt traditional ethics to modern life, the value of filial piety will only be retained at a negative level.…”
Section: Introductionmentioning
confidence: 99%
“… Yan and Chen (2018) focused on studying the relation between filial piety and life satisfaction of 481 Taiwanese college students and confirmed that both RFP and AFP had a positive association with life satisfaction. Research by Guo et al (2022) on middle school students and their parents about the relationship between RFP and AFP showed that RFP was positively correlated with school achievement. On the other hand, AFP was found to be negatively correlated with academic achievement, but not correlated with children’s perceived happiness.…”
Section: Introductionmentioning
confidence: 99%